KORELASI ANTARA PERILAKU MAKAN DENGAN PENINGKATAN BERAT BADAN SELAMA PROSES PEMBELAJARAN DARING PADA MAHASISWA KEDOKTERAN - NUR AINI DJUNET (JURNAL ILMIAH SIMANTEK, 2022)
Obesity is a chronic disease that is growing in many countries. Eating behavior affects individual energy intake. Emotional eating behavior and night eating syndrome (NES) describe eating behavior. The COVID-19 pandemic has forced students to undergo online learning since March 2020. We want to know student eating behavior and its correlation to weight gain in online learning. It was a cross-sectional study involving 100 first-year students in the Faculty of Medicine Universitas Islam Indonesia (FMUII). Emotional eating behavior was measured using the Palatable emotional motives eating scale (PEMS) and the NES with the Night eating disorders questionnaire (NEDQ). The diagnosis of NES was if the questionnaire score at ≥25. The student’s body weight increased by 3(0-30) kg for one year of online learning. The number of obese students increased from 20% to 31%. There were 82% of students with NES, and most of them got it in the last 6-12 months. There was a correlation (p<0.001) between the incidence of NES with an increase in the respondent's weight and a weak positive correlation (r=0.208; p<0.05) between emotional eating behavior during negative emotions and an increase in the respondent's weight. We conclude that the period of online learning affects eating behavior and is associated with student weight gain.